SIFO 1987: Motorism and the environment - Swedish Institute of Public Opinion Research; Din Bil (motor magazine) (Swedish Institute of Public Opinion Research, 1993)
This study, carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of the motor magazine Din Bil, examines opinions on most important reason for pollution of the environment, attitude toward heavier environmental demands on cars, and on inner-city traffic limitations. The respondents were also asked about changes already made in one owns driving and changes one is prepared to do for improving the environment. Background variables include information on gender, age, Swedish citizenship, occupation, private or public sector, trade union, right to vote in general elections, voting habit, political party preference and party voted for in 1985.

This study, carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of the motor magazine Din Bil, examines opinions on most important reason for pollution of the environment, attitude toward heavier environmental demands on cars, and on inner-city traffic limitations. The respondents were also asked about changes already made in one owns driving and changes one is prepared to do for improving the environment. Background variables include information on gender, age, Swedish citizenship, occupation, private or public sector, trade union, right to vote in general elections, voting habit, political party preference and party voted for in 1985.
SIFO 1987: Bilism och miljön
Keywords: ENVIRONMENT; MILJÖ; CARS; BILAR; Environment and conservation; Miljö och naturvård; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap